2011
DOI: 10.1002/hup.1209
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant medication of psychoses in a lifetime perspective

Abstract: ObjectivePatients treated with antipsychotic drugs often receive concomitant psychotropic compounds. Few studies address this issue from a lifetime perspective. Here, an analysis is presented of the prescription pattern of such concomitant medication from the first contact with psychiatry until the last written note in the case history documents, in patients with a diagnosis of psychotic illness.MethodsA retrospective descriptive analysis of all case history data of 66 patients diagnosed with schizophrenia or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 82 publications
0
12
0
Order By: Relevance
“…Therefore, the co-prescription of benzodiazepines with antipsychotics for schizophrenia patients should be monitored. Vares et al18) observed that, at some point, almost all patients (95%) in their study had been co-prescribed antipsychotics and benzodiazepines but that these treatment periods were short, at only ~14% of the total duration of antipsychotic medication. Given that in the present study there was a risk of increased mortality and limited information regarding the duration of polypharmacy relative to the total time of antipsychotic use, further studies will be needed to evaluate this point.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Therefore, the co-prescription of benzodiazepines with antipsychotics for schizophrenia patients should be monitored. Vares et al18) observed that, at some point, almost all patients (95%) in their study had been co-prescribed antipsychotics and benzodiazepines but that these treatment periods were short, at only ~14% of the total duration of antipsychotic medication. Given that in the present study there was a risk of increased mortality and limited information regarding the duration of polypharmacy relative to the total time of antipsychotic use, further studies will be needed to evaluate this point.…”
Section: Discussionmentioning
confidence: 89%
“…According to Vares et al18) most patients with psychosis have been prescribed a combination of medications at some point but the treatment periods were relatively short, corresponding to 14% of the total time of antipsychotics treatment, apart from anti-parkinsonism drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, factors such as maternal age, weight, smoking and alcohol consumption cannot be satisfactorily addressed. Additionally, the significance of concomitant medication such as more than one AP, antidepressants, anticonvulsants or anxiolytics, all of which remain common in clinical practice , also remains largely unaccounted for. Publication bias relevant to this MiniReview is likely to be conservative in terms of relative risk estimates; that is, incident cases are more likely to be published than cases or small series with no malformations.…”
Section: Discussionmentioning
confidence: 99%
“…FGA are known to cause a variety of extrapyramidal symptoms, whereas SGA have been associated with weight gain and metabolic side effects. Add-on drugs are common 15 and may relieve side effects. Although antipsychotics emerged in the 1950s with FGA and 1980s with SGA, the long-term consequences of these drugs and their respective add-ons on brain structure are still largely unknown.…”
Section: Introductionmentioning
confidence: 99%